2019
DOI: 10.1002/pat.4809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different ionic layered compounds decorated with zinc hydroxystannate on flame retardancy and smoke performance of epoxy resin

Abstract: ZHS@ Mg‐Al‐LDH and ZHS@α‐ZrP hybrid materials were prepared by electrostatically loading zinc hydroxystannate (ZHS) on the layered compounds (Mg‐Al‐LDH and α‐ZrP) in this work. With the addition of 2 wt% of the two hybrid materials to epoxy resin (EP), respectively, the fire hazard of EP and its composites were investigated. The limiting oxygen index (LOI) of ZHS@ Mg‐Al‐LDH/EP composite increased by 19.0% compared with pure EP, while its peak heat release rate (PHRR), total heat release rate (THR), and peak sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Ion-exchange in ZrP occurs at the Brönsted acid groups (P-OH) which are also present at the surface of the nanoparticles, opening another pathway for the modification of this material: surface modification [ 9 , 10 , 11 ]. These composite materials have been used for several applications including photocatalysis [ 12 , 13 ], drug delivery [ 14 , 15 , 16 , 17 ], amperometric biosensors [ 18 , 19 , 20 ], catalysis [ 7 , 21 , 22 , 23 , 24 , 25 , 26 ], flame retardancy [ 27 , 28 , 29 ], and others. We encourage the reader to also see other recent reviews on the topic of the synthesis of ZrP and its applications [ 7 , 8 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ion-exchange in ZrP occurs at the Brönsted acid groups (P-OH) which are also present at the surface of the nanoparticles, opening another pathway for the modification of this material: surface modification [ 9 , 10 , 11 ]. These composite materials have been used for several applications including photocatalysis [ 12 , 13 ], drug delivery [ 14 , 15 , 16 , 17 ], amperometric biosensors [ 18 , 19 , 20 ], catalysis [ 7 , 21 , 22 , 23 , 24 , 25 , 26 ], flame retardancy [ 27 , 28 , 29 ], and others. We encourage the reader to also see other recent reviews on the topic of the synthesis of ZrP and its applications [ 7 , 8 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the decomposition of hydroxyl groups in the ZHS and NCH, as well as the release of water and anions from the NCH interlayer, diluted the flammable volatiles in the flame zone and also acted as a flame retardant in the gas phase. To enhance the flame retardant and smoke suppressive properties of EP, ZHS@Mg-Al-LDH and ZHS@α-ZrP were prepared by co-precipitation method through electrostatic interaction, which was added into EP [ 64 ]. The LOI of ZHS@Mg-Al-LDH/EP and ZHS@α-ZrP/EP presented an enhancement of 25.7% and 26.0% compared with neat EP.…”
Section: The Application Of Zhs-based Flame Retardantmentioning
confidence: 99%
“…For the XRD curves of ZHS, the typical characteristic peaks appeared at 2θ of 19.8 , 33.5 , 32.7 , 36.6 , 40.3 , 46.9 , 52.8 , 58.3 , and 68.4 . They corresponded to the (1 1 1), (2 0 0), (2 2 0), (3 1 0), (2 2 2), (4 0 0), (4 2 0), (4 2 2), and (4 4 0) crystal planes of ZHS, 29 respectively. In addition, the sharp crystal shape indicated that The chemical compositions of FMH, FMH@ZHS, and ZHS were further confirmed by XPS, and the results were shown in Figure S3.…”
Section: Characterization Of Fmh Zhs and Fmh@zhsmentioning
confidence: 99%